STUDI KASUS TENTANG PERILAKU RENDAH DIRI PADA PESERTA DIDIK - Sherend Irma; Abas Yusuf; Purwanti Purwanti (Universitas Tanjungpura, 2020)
AbstractThe general objective in this research is to get clarity in how to help students who have inferiority in class X SMA Negeri 6 Pontianak. This research method is descriptive in the form of case study research. The case subjects in this study were two people. Data collection techniques in this study were observation and interview. The research data collection tools are observation guide and interview guides. To overcome the problems experienced subjects I and II, an approach from the Adlerian counseling model is a reeducation process for case subjects in an effort to change their perceptions and social values that are not true and re-new their motivational orientation. The techniques used is Assessment technique,Guided and Imagery technique, Role Playing technique, and Socratic Questioning technique. The result obtained after being given alternative help on the case subject one, experienced many changes, especially in socializing,such as being good communication,but not able to explore the capabilities they have. Whereas the subject of case two felt that there was no visible change in himself and still felt that she was not considered there by her friends. Researcher's suggestion in that case subjects are expected to be able to maintain and increase positive changes.Keywords :Case Studies, Inferiory Feelings, Adlerian